2018
DOI: 10.1164/rccm.201705-0894le
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Children with Mild Cystic Fibrosis Using Hyperpolarized Gas Lung Magnetic Resonance Imaging and Lung Clearance Index

Abstract: IntroductionImproving life expectancy in patients with cystic fibrosis (CF) alongside annual rates of decline in FEV1 as low as 1-2% predicted per year (1), poses challenges for the use of spirometry as a measurement of longitudinal change. Spirometry is also insensitive to early changes in the CF lung, and lung clearance index (LCI) derived from multiple breath washout (MBW) has emerged as a promising alternative in patients with well-preserved spirometry, including children (2).Recently the potential of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 10 publications
1
57
0
2
Order By: Relevance
“…7 Ventilation defect percent is reproducible over short time periods (i.e., up to a few weeks) in patients with CF with stable health, 8 and longitudinal imaging (i.e., up to a few years) can identify functional changes that are not reflected in PFTs. 9,10 In addition, VDP is strongly correlated with LCI, and this result has been confirmed using HP 129 Xe 11,12 and 3 He MRI. 13 It has been suggested that both VDP and LCI probe similar physiology, as VDP visualizes the spatial heterogeneity of ventilation during a static breath-hold at a single time-point following a single HP gas inhalation, and LCI measures the temporal heterogeneity of the tracer gas washout (i.e., nitrogen [N 2 ] or sulfur hexafluoride [SF 6 ]) during multiple exhalations.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…7 Ventilation defect percent is reproducible over short time periods (i.e., up to a few weeks) in patients with CF with stable health, 8 and longitudinal imaging (i.e., up to a few years) can identify functional changes that are not reflected in PFTs. 9,10 In addition, VDP is strongly correlated with LCI, and this result has been confirmed using HP 129 Xe 11,12 and 3 He MRI. 13 It has been suggested that both VDP and LCI probe similar physiology, as VDP visualizes the spatial heterogeneity of ventilation during a static breath-hold at a single time-point following a single HP gas inhalation, and LCI measures the temporal heterogeneity of the tracer gas washout (i.e., nitrogen [N 2 ] or sulfur hexafluoride [SF 6 ]) during multiple exhalations.…”
Section: Introductionmentioning
confidence: 62%
“…Ventilation defect percent is reproducible over short time periods (i.e., up to a few weeks) in patients with CF with stable health, and longitudinal imaging (i.e., up to a few years) can identify functional changes that are not reflected in PFTs . In addition, VDP is strongly correlated with LCI, and this result has been confirmed using HP 129 Xe and 3 He MRI .…”
Section: Introductionmentioning
confidence: 65%
“…More broadly, these results suggest that elevated MBW indices induced by airway constrictions are more variable in general, which is observed experimentally in CF and asthma patients through the increased sensitivity of LCI to posture [36,37], as well increased inter-patient variability [38].…”
Section: Discussionmentioning
confidence: 55%
“…More broadly, these results suggest that elevated MBW indices induced by airway constrictions are more variable in general, which is observed experimentally through the increased variance in LCI measured in CF and asthma patients [46], as well as an increased sensitivity of LCI to posture which affects the distribution of ventilation due to gravity [47,48]. This latter affect can be understood by perturbing acinar elastance, which affects their rate of ventilation.…”
Section: Discussionmentioning
confidence: 67%
“…As researchers and clinicians consider the potential applications of inert fluorinated gas MRI, rigorous reproducibility and validation studies will be required. HP gas MRI technology is maturing, and instead of focusing on developing new acquisition approaches, investigators are now focusing on longitudinal imaging 77 and interventional trials with novel therapeutics. 78 19 F MRI technology is not currently as well-developed as HP gases, but there is a strong potential for using it in similar applications in the future.…”
Section: Discussionmentioning
confidence: 99%